2021
DOI: 10.3390/ani11082228
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Recovery of Turbot (Scophthalmus maximus) Sedated with MS-222 and Eugenol: Effects on Intermediary Metabolism and Osmoregulation

Abstract: This study focused on the anesthetic waterless keep-alive transport technique for turbot. MS-222 and eugenol were used to anesthetize turbot and then the waterless keep-alive transport was conducted. The blood physiological changes and flesh quality changes of turbot were evaluated after cooling and during the simulated waterless transport. The results show that the temperature lowered from 13 to 2 °C, resulting in a decrease in moisture, fat and protein contents of all samples. Compared to the control turbot,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similarly, Cao et al (2021) found that MS-222 and eugenol-anesthetised turbot (Scophthalmus maximus) has lower blood glucose and cortisol level than the control (non-anesthetised) groups. Navarro et al (2016) also stated that plasma cortisol and glucose of the anaesthetized O. niloticus were lower than those of untreated controls.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Cao et al (2021) found that MS-222 and eugenol-anesthetised turbot (Scophthalmus maximus) has lower blood glucose and cortisol level than the control (non-anesthetised) groups. Navarro et al (2016) also stated that plasma cortisol and glucose of the anaesthetized O. niloticus were lower than those of untreated controls.…”
Section: Discussionmentioning
confidence: 86%
“…The body maintains a relatively constant glucose concentration through the synthesis and catabolism of liver glycogen [ 46 ]. Previous studies have shown that aquatic animals respond to the stress of low temperatures and transport by breaking down liver glycogen to maintain the body’s energy requirements [ 47 , 48 ]. Eugenol has also been found by previous studies to relieve transportation stress, with significantly reduced serum levels of COR (cortisol) and GOT (glutamic oxaloacetic transaminase) found in hybrid amazon catfish ( Pseu-doplatystoma reticulatum × Leiarius marmoratus ) anesthetized by eugenol [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six groups were used in this study. The concentrations of MO in the transport water were 10 (10 MO), 20 (20 MO), and 40 (40 MO) mg/L; MS-222 was 30 mg/L (MS-222) [28]; and eugenol was 20 mg/L (Eugenol) [29], respectively. The character of MS-222 was weakly acidic, and the pH value range of the transport water after adding 30 mg/L MS-222 was 7.0~8.0.…”
Section: Live Transport Experimental Designmentioning
confidence: 99%